Music and Soviet power, 1917-1932 - Frolova-Walker, Marina; Walker, Jonathan (Pianist) (Boydell Press, 2012)
The book not only provides a detailed and nuanced depiction of the early Soviet musical landscape, but brings it to life by giving voice to the leading actors and commentators of the day. The vibrant public discourse on music is presented through a selection of press articles, reviews and manifestos, all supplied with ample commentary. These myriad sources offer a new context for our understanding of Shostakovich, Prokofiev and Myaskovsky, while also showing how Western music was received in the USSR.